Cajamarca pilot foresty with tara - Rojas Lazo, Oswaldo (2010)
In the last years, because of the variety of industrial applications of the tara`s fruit (the shell and the seeds can be processed to obtain a lot of products), the interest on cultivate tara using correct techniques is enhanced. This project of forestation with tara is carried out in Cajamarca Department (years 2008-2009), San Juan district, Cachilgon country house, which population has 40% of adults without instruction. They are dedicated to the foodstuffs agriculture and earn money with recolectation of the fruit of the tara, where the tara grows as a wild tree. To show to the population the facility of handling the agriculture of the tara and its economical profitability, it has being develop this pilot project of forestation with 1 546 tree of tara, which requires an initial investment of 12 243 peruvian soles, an annual referential cost of 4 720 peruvian soles and recover all the investment in 2012.